Burundi : Enhanced Heavily Indebted Poor Countries Initiative; Completion Point Document and Multilateral Debt Relief Initiative. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This paper discusses the progress made by Burundi under the enhanced Heavily Indebted Poor Countries (HIPC) Initiative. Burundi has made satisfactory progress in achieving the completion point triggers. It has fully implemented the triggers on preparing and implementing a Poverty Reduction Strategy Paper (PRSP) and maintaining a stable macroeconomic environment. The paper recommends that the Executive Directors of the International Development Association (IDA) and the IMF approve the completion point for Burundi under the enhanced HIPC Initiative.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet